Psychological empowerment of the youth’s at Tsungirirai welfare organization in Norton - Chazuka, Hillary (Midlands State University, 2019)
The study of psychological empowerment have been neglected locally,regionally and internationally. Different empowerment programs that have been introduced worldwide have failed to address the matter from a psychological standpoint. Negligence of psychological empowerment programes globally has therefore contributed to high rate of unemployment amongst the youth’s.The fact that the youth’s are the most disadvantaged group drive the researcher to carry out a study that targeted the youth’s.The purpose of the study is to assess the psychological empowernment characteristics amongst the youth’s and as well as to examine whether psychological empowerment differs by age,gender,socio-economic status and religion. In order to unpack the concept of psychological empowerment quantitative research approach was employed.Descriptive survey method was adopted by the researcher as the research design.Data was collected using convenience sampling technique targeting 120 youths, 78 being females and 42 being males. The condensed version questionnaire of psychological empowerment by Zimmerman et al (1991) was used by the researcher to obtain information from the participants. Data was analysed using the statistical package for social sciences version 16.0. The study established that psychological empowerment differs by gender,age,religion and socio-economic status. Conclusively the research discovered that psychological empowernment aspects such as self efficacy, assertiveness, interpersonal confidence and perceived socio-political control are influenced by innate and inherent factors. The researcher recommend empowerment policy makers and implementers to also include psychological empowernment programmes locally and regionally so as to uplift the status of the youth’s. Psychological empowerment should have clear policies that govern the appropriate implementation of these programmes.